NEW CONCEPT FOR DIGITAL INCLUSION—ONLINE AND MOBILE LEARNING PROGRAMS FOR OLDER PERSONS - Lipphardt, Anne-Marie; Leen-Thomele, Eline; Coroian, Anamaria Elena; Held, Paul (Innovation in Aging, 2017)
This paper sums up the evaluation results of two e-learning ICT courses for older adults: a tablet computer course and a regular computer course, and discusses the advantages of mobile learning and e-learning for older adults. As part of an European research project, the SenApp project, online course modules were developed, to teach older adults the first steps on a tablet computer, and evaluated (N=37, age range 58–93). The other course we analyzed, was an online learning course with regular computers and part of the LernHaus project in Germany (N=29, age range 50–89). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that all courses were rated good, compliance was very good and that support was a key factor for course success. Mobile learning was slightly easier for new learner